PAJAK PENGHASILAN PASAL 21 (STUDI KASUS PADA PT GRAZINDO ASIA PERKASA JAKARTA) - Setiadi Hartoko (JURNAL LENTERA AKUNTANSI, 2016)
ABSTRACT Tax is a compulsory contribution to a country owed by an individual or a coercive body under the Act, By not reciprocating directly and used for the purposes of the state for the greatest prosperity of the people. Research methodology with direct observation and literature through interview. Calculation, Deposit, reporting until recording is conducted in accordance with Taxation Law no. 36 of 2008 and for listing in accordance with PSAK No. 46 Keywords : PPh Pasal 21, UU No 36 / 2008, Hitung – Setor - Lapor – Catat.